Pengaruh Desain Interior Terhadap Kenyamanan Pengunjung Di Museum Adityawarman Provinsi Sumatera Barat - Silvia Febriani; Heldi Heldi (Jurnal Kajian dan Penelitian Umum, 2023)
The study aims to determine (1) Is there an effect of interior design on visitor comfort at the Adityawarman Museum of West Sumatra Province. (2) Interior design elements that have a dominant and significant effect on visitor comfort at the Adityawarman Museum, West Sumatra Province. This type of research is quantitative research using the description method. The technique used for data collection in this study used a questionnaire (questionnaire) using a Likert scale to score each question item. The population in this study amounted to 1895 visitors and a sample of 95 visitors, sampling was carried out by accidental sampling technique. Based on the research results, overall interior design has a significant effect on visitor comfort at the Adityawarman Museum. It can be seen from data processing using SPSS version 25.0, showing that the Fcount value is 10.112> Ftable 3.94 and a significant value of 0.002 < α = 0.05. The variable interior design element that has the most dominant effect on visitor comfort at the Adityawarman museum is the ceiling with a total average score of 4.29 on the interval scale 4.24-5.04 "very good".